Pembangunan Pariwisata Daerah di Kabupaten Pringsewu: Perspektif Pariwisata Berbasis Komunitas dan Penghidupan Berkelanjutan - Singgalen, Yerik Afrianto; Nugroho, A. Y. Agung; Suharsono; Nantingkaseh, Alfonso Harrison (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2023)
Institutionally, the Tourism Awareness Group (Pokdarwis) has encouraged community participation in each village (pekon) to optimize the potential of natural, cultural, and human resources as tourist attractions. This study aims to describe in-depth the dynamics of the collaboration of the Tourism Awareness Group in Pringsewu Regency to increase public awareness in each village about the benefits of the tourism sector for the sustainability of household livelihoods, preservation of social-cultural values, and environmental sustainability. This study uses a community-based tourism perspective. Meanwhile, the qualitative research method with a case study approach is used for three tourist objects developed by Pokdarwis, namely Akasia valley, Talang Indah, and Teluk Kenyo. Retrieval of research data is conducted using in-depth interviews, observation, and document study while, data processing uses triangulation techniques to obtain valid and credible information. This study indicates that Pokdarwis in each village (pekon) are organized because the Pokdarwis Communication Forum is the central organization that connects 37 Tourism Awareness Groups throughout the Pringsewu Regency, Lampung Province. Proactively, Forkom Pokdarwis establishes communication with the government, local entrepreneurs, academics, and rural communities to optimize natural, cultural, and human resources by pioneering tourist destinations. Several tourist destinations have successfully pioneered and developed through reasonable assistance and coordination, opening up local communities' job opportunities.